The Hepatoprotective Effect of Moringa oleifera Leaves on Male Wistar Rat Induced Streptozotocin-Nicotinamide - Bachri, Moch Saiful; Nurani, Laela Hayu; Edityaningrum, Citra Ariani; Ma'ruf, Muhammad; Sulistyorini, Dwi Agustin; Amelia, Rizki; Hidayati, Sholihatil; Sulistyawati, Rini; Guntarti, Any (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Diabetes mellitus is a disease characterized by uncontrolled increases in blood sugar levels, which can cause complications in the liver. Disorder liver disease can be seen from the increasing SGOT, SGPT activity, and the number of necrosis cells in the liver. Moringa leaves contain the flavonoid quercetin with antidiabetic and antioxidant activity. This research aimed to determine the effect of administering the ethyl acetate fraction of Moringa leaves on SGOT activity, SGPT, and liver histopathology in rat induced by streptozotocin and nicotinamide. Moringa leaves macerated with 80% ethanol and fractionated with ethyl acetate were used. The research subjects were 30 rats divided into six groups. The rats were induced with streptozotocin at a dose of 65 mg/kgBW and nicotinamide 100 mg/kgBW for five days, then treated for ten days. Serum SGOT and SGPT activity were measured using a Microlab 300 Semi-Automated at a wavelength of 340 nm. Histopathological observations were carried out when the rats were dislocated, their livers were taken, and then preparations were made using Hematoxylin Eosin (HE) staining. Data were analyzed using the SPSS One Way ANOVA method, followed by the Tukey test with a confidence level of 95%. The results of the study showed that administration of Ethyl Acetate Fraction of Moringa oleifera (EA-MO) could reduce the levels of SGOT, SGPT, and the number of liver necrosis cells in rats induced by streptozotocin and nicotinamide.